Od individualnega do javnega (precedenčnega) namena Vrhovnega sodišča - Zobec, Jan (Podjetje in delo, 2015)
It is not possible for the Supreme Court to serve simultaneously, and to the same extent, both the private and the public purpose of adjudication. As practice has shown, restrictions of access to the Supreme Court are inevitable, since hyperproduction of its case law (when even the Court which created it loses its memory), leads to normative chaos. For this reason the Slovenian legislature decided to adopt (not wholly, yet just partly) the "leave to appeal system", which entails that the role of the Supreme Court is that of creating precedents. What is necessary to ensure that role is the possibility that the Supreme Court may omit reasons in orders denying leave to appeal. The Constitutional Court rejected the motion challenging the legal provision providing for omission of reasoning in the decisions denying leave to appeal and hence preserved the "leave to appeal system". And clearly stated: Less is more. For the full-fledged precedential role of the Supreme Court to flourish, however, further steps should be necessary - the steps of normative, organizational and meta-normative nature.
Keywords: pooblastila; pravosodje; pristojnosti; revizija; sodna praksa; sodne odločbe; vrhovna sodišča